Religious Endowments as a Financing Mechanism for Cancer Patients in Algeria: A Comparative Analytical Approach - Aouda, Bouadma; Dey , Sarra; Nouh , Ferroudji; Zahra , Blal Fatima (Journal of Ecohumanism, 2025)
This study aims to analyze the potential of religious endowments (awqaf) as an innovative and sustainable mechanism for financing cancer treatment in Algeria, through a comparative analytical approach with Malaysian and Turkish experiences. The findings reveal that Algeria, despite possessing a rich waqf heritage, does not utilize endowments in the healthcare sector, unlike Malaysia and Turkey, which have successfully activated health waqf through flexible legislative frameworks and effective governance. The study recommends reforming the legal framework for waqf in Algeria, establishing an independent health waqf authority, launching awareness campaigns, and forming international partnerships to support this initiative.